2019
DOI: 10.1177/0031512519880421
|View full text |Cite
|
Sign up to set email alerts
|

Altered Visual and Proprioceptive Spatial Perception in Individuals with Parkinson’s Disease

Abstract: Difficulties in the integration of visual, vestibular, and somatosensory information in individuals with Parkinson’s disease (PD) may alter perception of verticality. Accordingly, in this cross-sectional study, we analyzed PD patients’ ( n = 13) subjective visual vertical (SVV) and subjective haptic vertical (SHV) perceptions and compared them to those of healthy controls ( n = 14). We compared SVV and SHV findings among participants with PD, healthy controls, and cutoff points of normality based on prior rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
12
0
4
Order By: Relevance
“…This study demonstrated that individuals with post-COVID-19 condition that were hospitalized showed less accurate performance for SVV and SHV than non-hospitalized individuals. Studies have evaluated the perception of verticality in individuals with acquired 36 and degenerative 31 diseases of the central nervous system (CNS). However, no previous studies have examined this variable in individuals with long-term COVID.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study demonstrated that individuals with post-COVID-19 condition that were hospitalized showed less accurate performance for SVV and SHV than non-hospitalized individuals. Studies have evaluated the perception of verticality in individuals with acquired 36 and degenerative 31 diseases of the central nervous system (CNS). However, no previous studies have examined this variable in individuals with long-term COVID.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] In addition, more severely ill patients undergoing hospitalization have a greater storm of pro-inflammatory cytokines in the acute phase, with an increased risk of developing a neurodegenerative condition. 46,47 Neurodegenerative processes can alter long-term verticality, 31 graviceptive information perception due to the reduced activity of somatosensory cortical areas. It can also be inferred that changes in verticality observed in this study may have been caused by changes in the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations